Factors influencing the attitudes of individuals in favor of sustainable development: a study with students in the field of management - Cruz, Thayse Santos da; Gomes, Sonia Maria da Silva; Figueiredo, Paulo Soares; Sampaio, Márcio Santos; Dias Filho, Jose Maria; Ferreira Neto, Jose Venancio (Revista de Administração da UFSM, 2020)
Purpose: This study aimed to identify factors influencing the attitudes of individuals towards sustainable development, in its different dimensions. Design/methodology/approach: For the scope of the study, were admitted students from presential courses in Administration and Accounting Sciences from two Higher Education Institutions (HEI) located in the State of Bahia. Questionnaire was used as the data collection instrument. For the test of hypothesis, a multiple linear regression analysis was made, with a data base of 254 questionnaires. Findings: There was evidence that the knowledge about sustainability influences, in a positive and significant way, the student attitude in Dimensions Environmental, Economic, Social and Education. Results indicate that students with left-wing political conceptions have a tendency of showing more positive attitudes regarding sustainable development in Social and Education Dimensions. Finally, evidence was obtained about negative and significant relation between family income with Environmental and Economic Dimensions. Research Implications: Conceptually, in this study a fourth dimension of attitudes regarding sustainability was incorporated to the traditional tripod of sustainability, thus transforming it in a tetrahedron. Practical Implications: The meaning and importance of those evidences are discussed and can contribute to generate policies on education for sustainability. Originality/value: The study contributes to enable a better understanding about the formative process, the conscience, the attitude and the behaviors around sustainability questions in the field of management, which are relevant for reaching one of the Sustainable Development Goals proposed by the United Nations.